THE EFFECTS OF TEACHING TECHNIQUES AND LANGUAGE ATTITUDE TOWARDS STUDENT’S SPEAKING SKLL (EXPERIMENT AT PRIVATE UNIVERSITY IN EAST JAKARTA) - Suwantica Kusumandari (LPPM Universitas Bina Sarana Informatika, 2019)
ABSTRACT The purpose of this study was to: determine the interactional effects of teaching technique and language attitude towards student’s speaking skill; determine the effect of teaching technique towards student’s speaking skill; determine the effect of language attitude towards student’s speaking skill; that were taught by role plays and filling information gap (both are communicative language teaching) to the students with different language attitudes. The research method used was experimental one. Sample size of 60 students consisting of 30 for experimental class and 30 for control class taken from Private University in East Jakarta, and the sampling technique used is cluster sampling. Research instruments used were the test to distinguish student’s language attitude in the form of preferential test (20 items) and speaking skill in the form of oral test (5 items for scoring), that have been tested valid and reliable with coefficient of reliability at 0.839 and 0.705. The research uses two-ways ANOVA test. The results showed: 1) There is a significant effect of teaching technique towards student’s speaking skill, as Fobserved = 95.553 > Ftable = 2.77 and Sig = 0.000 < 0.05. 2) There is a significant effect of language attitude towards student’s speaking skill as Fobserved = 10.617 > Ftable = 2.77 and Sig = 0.002 < 0.05. 3) There are significant interactional effects of teaching technique and language attitude towards student’s speaking skill as Fobserved = 8.199 > Ftable = 2.77 and Sig = 0.006 < 0.05. 4) The group of students with positive language attitude would achieve more in speaking skill compared to another groups of language attitude if taught by using role plays technique. The results contribute most to the increasing of student’s speaking skill. Keywords: Teaching Technique, Language Attitude, Speaking Skill